Google Scholar, Web of Science, and Scopus: A systematic comparison of citations in 252 subject categories - Martín-Martín, Alberto; Orduna-Malea, Enrique; Thelwall, Mike; Delgado López-Cózar, Emilio (Journal of informetrics, 2018)
•Google Scholar found nearly all citations found by WoS (95%) and Scopus (92%), and a large amount of unique citations.•About half of Google Scholar unique citations are not from journals. A significant minority (19–38%) are not in English.•Google Scholar unique citations have, on average, a much lower scientific impact than citations also found by WoS/Scopus.•Spearman correlations of citation counts between Google Scholar and WoS/Scopus are strong across all subjects (0.78–0.99). Despite citation counts from Google Scholar (GS), Web of Science (WoS), and Scopus being widely consulted by researchers and sometimes used in research evaluations, there is no recent or systematic evidence about the differences between them. In response, this paper investigates 2,448,055 citations to 2299 English-language highly-cited documents from 252 GS subject categories published in 2006, comparing GS, the WoS Core Collection, and Scopus. GS consistently found the largest percentage of citations across all areas (93%–96%), far ahead of Scopus (35%–77%) and WoS (27%–73%). GS found nearly all the WoS (95%) and Scopus (92%) citations. Most citations found only by GS were from non-journal sources (48%–65%), including theses, books, conference papers, and unpublished materials. Many were non-English (19%–38%), and they tended to be much less cited than citing sources that were also in Scopus or WoS. Despite the many unique GS citing sources, Spearman correlations between citation counts in GS and WoS or Scopus are high (0.78-0.99). They are lower in the Humanities, and lower between GS and WoS than between GS and Scopus. The results suggest that in all areas GS citation data is essentially a superset of WoS and Scopus, with substantial extra coverage.